STUDIES ON TOXOPLASMOSIS IN HORSES IN KHARTOUM STATE-SUDAN - Ishag, Manal Y; Majid, AM.; Abuobeida, MM. (Journal of Veterinary Medicine and Animal Production, 2021)
The aim of this study was to determine the seroprevalence of Toxoplasma. gondii antibodies among horses in Khartoum state and to report the role of T. gondii in abortion in equines T gondii tachyzoites and oocysts were isolated from an aborted foal. Sera from 381 clinically healthy horses at different locations in 3 cities (Khartoum, Omdurman and Khartoum North) were tested for the presence of T. gondii antibodies using ELISA test. IgG antibodies of T. gondii were detected in 24 out of 381 (6.3%) , while IgM antibodies of T. gondii were detected in 2 horses out of 381 (0.5%). Antibodies titers were found in 10 horses at 1: 20 dilution , in 7 horses at 1:40 dilution , in 5 horses at 1:80 dilution ,and in 2 horses at 1:160 dilution. There are no significant differences (P<0.5 ) within sex . Horses in the three cities were positive with higher prevalence in Omdurman city: 12 (10%) out of 120 horses , followed by Khartoum city : 9(5.9%) out of 153 horses. Khartoum North City , showed the lowest prevalence with 3 positive samples (2.8%) out of 108 horses.